Ubiquitous Computing - Gestures Interaction Applied the Learning Disabilities in Process Literacy - Oliveira, Danielle Teixeira; Carvalho, Marla Dore; Paixão, Tuane Lisboa Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
This article uses the interaction of gestures and learning concept with mobility or mobile learning (M-Learning) to propose a mobile platform based on manipulation gestures focusing on benefit children in the literacy process in early childhood education to submit a learning disability. Based on ubiquitous computing and better usability, the objective is to make children can learn while playing through the manipulation of objects in touchscreen